Structural Analysis and Design the municipality of Nablus - Alaa Ismael Nmr Abdullah; Amara Rashad Kamil Baghdadi; Yosra Hani Mahmoud Ajaj (My University, 2021)
The name of the project is the municipality of Nablus, as it is a proposed project (not existing), which is located in the center of Nablus, next to Jamal Abdel Nasser Park. Whereas, the aim of establishment is to collect all sections of the municipality in one building and to solve the problem of congestion in the old building. The building consists of 9 floors, with a total area of 991.765 m2. The majority of the building area is classified into various offices and service rooms, such as electricity, water, sewage and other departments. The basement consists of parking with an area of 228.975 m2. The ground floor has security, fees collecting hall, Multiple room…etc. with an area 228.975 m2. In addition, the first floor has canteen, mayor’s office, meeting room ... etc. with a total area 228.975 m2, followed of second, third, fourth and fifth floors, all of them have the same area 63.06 m2 also that contain different rooms such as (surveying, planning, construction, electricity, water and sewerage... etc.). Finally, the sixth and seventh floors have the same area 26.3 m2 and contain of studies and court. Structure models will be analyzed and designed using the SAP2000 software, and the results will be checked by hand calculation. In addition, structural plans related to the structure and reinforcement sections will be drawn using AutoCAD, which will be designed based on ACI318-14 code and seismic design of the structure on the IBC code.